2020
DOI: 10.3390/cancers12102973
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Translocator Protein TSPO in Hallmarks of Glioblastoma

Abstract: Glioblastoma (GBM) is the most fatal primary brain cancer in adults. Despite extensive treatment, tumors inevitably recur, leading to an average survival time shorter than 1.5 years. The 18 kDa translocator protein (TSPO) is abundantly expressed throughout the body including the central nervous system. The expression of TSPO increases in states of inflammation and brain injury due to microglia activation. Not least due to its location in the outer mitochondrial membrane, TSPO has been implicated with a broad s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 216 publications
(294 reference statements)
2
48
0
Order By: Relevance
“…Previous clinical research revealed that TSPO expression levels are elevated in various cancers including glioma [ 24 , 25 ], and increased TSPO expression was positively correlated with poor prognosis, as observed in our present study. In fact, the biological function of TSPO in glioma cells had been widely studied.…”
Section: Discussionsupporting
confidence: 88%
“…Previous clinical research revealed that TSPO expression levels are elevated in various cancers including glioma [ 24 , 25 ], and increased TSPO expression was positively correlated with poor prognosis, as observed in our present study. In fact, the biological function of TSPO in glioma cells had been widely studied.…”
Section: Discussionsupporting
confidence: 88%
“…A variety of MRI and PET imaging techniques have been used to quantify TAMs in gliomas (43), for example, in a pilot study of 10 adult subjects with GBM who underwent ferumoxytol-enhanced MRI, measurements of susceptibility obtained after ferumoxytol administration correlate with iron-containing macrophage concentration (34); however, this approach requires slow intravenous administration of ferumoxytol followed by next day delayed imaging which may limit the widespread use. Translocator protein (TSPO) speci c PET radiotracers have also been used to monitors TAMs; however, the two main limitations are lack of phenotype (M1 vs. M2) speci city (43), and over-expression in tumor cells (44). To the best of our knowledge, our study is the rst to provide both in vivo and ex vivo evidence for the application of non-invasive MRI imaging for TAMs quanti cation and spatial mapping in human GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the authors supported [ 18 F]DPA-714 PET imaging as an imaging readout for the degree of immunosuppressive myeloid cell infiltration. On the other hand, Pannell et al investigated whether TSPO upregulation in astrocytes and microglia/macrophages was restricted to a specific phenotype [44]. TSPO overexpression was observed both in vitro and in vivo after injection of TNF-inducing adenovirus while no change was observed after IL-4 stimulation, correlating with [ 18 F]DPA-714 PET signal.…”
Section: Glioma-associated Inflammationmentioning
confidence: 99%
“…Overall, considering the role of TSPO in the regulation of GBM development, the interpretation of the TSPO PET signal is still challenged by the time-dependent cellular sources and functions of TSPO [44]. One recent study by Fu et al (2020) indicated that TSPO appears as a key regulator of glioma growth and especially angiogenesis through the regulation of mitochondrial oxidative phosphorylation and glycolysis [30].…”
Section: Other Featuresmentioning
confidence: 99%